Pendampingan Pelaporan Perpajakan Bagi Wajib Pajak UMKM Desa Morowudi Kecamatan Cerme Kabupaten Gresik - Mutiara Rachma Ardhiani; Sutama Wisnu Dyatmika; Wira Yudha Alam; Yuni Sukandani; Siti Istikhoroh (Ekobis Abdimas, 2022)
Micro, Small and Medium Enterprises are one of the drivers of the Indonesian economy. This large contribution of MSMEs is in contrast to tax revenues from the MSME sector. There are several things that cause state revenue from this sector to not be maximized. One reason is that not a few MSME actors have limited ability to fulfill their tax rights and obligations. Limited knowledge is one of the obstacles to the development of MSMEs. MSMEs need the role of various parties who can educate and assist them to improve their compliance in paying taxes. Based on this, community service activities are carried out in the form of tax socialization and assistance to MSMEs with the hope of helping MSMEs in fulfilling their tax obligations.